Microstructure and in-plane component of L10-FePt films deposited on MgO and MgAl2O4 substrates. (15th March 2017) - Sepehri-Amin, H.; Iwama, H.; Ohkubo, T.; Shima, T.; Hono, K.
Abstract: Microstructures of FePt films deposited on MgO and MgAl2 O4 single crystalline substrates were studied using aberration corrected scanning transmission electron microscopy (STEM). The [100] and [010] variants of L10 -FePt were observed in-the-plane of the FePt grains deposited on the MgAl2 O4 substrate, which causes in-plane component in magnetization curves. The d-spacing of the (002) planes of L10 -FePt deposited on MgAl2 O4 is larger than that deposited on MgO. The reduction of lattice mismatch between FePt and the substrate results in the formation of out-of-plane tensile strain leading to increase in d 002 and the formation of the in-plane variants in the L10 -FePt grains. Graphical abstract: